Sleep Disturbances in Depressed and Non-Depressed Pregnant Women - Okun, Michele L. (2011)
BACKGROUND: Sleep disturbances and symptoms of depression are common during pregnancy. Both are independent and interrelated risk factors for adverse outcomes. It is unclear the degree to which sleep differs between depressed and non-depressed pregnant women. We sought to 1), describe and compare sleep disturbances in depressed pregnant and non-depressed pregnant women, 2) determine the impact of selective serotonin reuptake inhibitors (SSRI) treatment on sleep, and 3)evaluate whether sleep at 20 weeks is associated with increased depressive symptoms and major depressive disorder (MDD) in later pregnancy. METHODS: Pregnant women (N = 240) were recruited in the second trimester (20 weeks gestation) and assigned to depressed (N = 59) and non-depressed (N = 181) groups based on a SCID diagnosis of major depressive disorder. The Structured Interview Guide for the Hamilton Rating Scale with Atypical Depression Supplement (SIGH-ADS) was administered at 20, 30 and 36 weeks gestation from which the sleep variables were obtained. RESULTS: Depressed women had more fragmented sleep at each assessment (p values ≤ .05). However, the frequency of insomnia symptoms was greater for depressed women only at 20 weeks gestation. SSRI use, regardless of MDD status, did significantly affect several sleep variables. Among the non-depressed women, those with short or longer sleep duration, symptoms of insomnia and long periods of nocturnal waketime had higher SIGH-ADS scores later in pregnancy (p values = < .05). CONCLUSIONS: At 20 and 30 weeks gestation sleep was more disturbed in depressed pregnant women compared to non-depressed pregnant women. At 36 weeks, sleep was disturbed regardless of depression status or SSRI use. Among the non-depressed women, disturbed sleep in conjunction with SSRI use was associated with higher depressive symptoms.